Prevalencia de hipertensión arterial y factores de riesgo asociados en la población adulta del HGZ/MF No. 2 de Zacapu, Michoacán - González Elias, Concepción Margarita (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
Arterial Hypertension (AHT) is a public health problem due to its high prevalence and as a risk factor for multiple diseases. Objective: To establish the prevalence of AHT and associated risk factors in the adult population of HGZ/MF No. 2 of Zacapu Michoacán. Material and Methods: Cross-sectional, observational and prospective study. Carried out at HGZ/MF No.2 from August to October 2022. The MMM21 questionnaire was applied to find out risk factors, endorsed by the International Society of Arterial Hypertension. Descriptive and X2 statistics were performed to determine the association between categorical variables with a significant value of p<0.05. Registration Number: R-2022-1603-005. Results: 325 subjects were studied, of which 126 (38.77%) already had a diagnosis of SAH and 73 (22.45%) presented BP figures greater than 140/90mmHg, finding a total prevalence of 61.22%, predominantly in the female sex. from 61-80 years. As associated risk factors, smoking, gestational diabetes, age and a history of heart disease were found, with AMI being the most frequent. Of the 126 subjects diagnosed with SAH, only 70.64% were under control. Conclusions: A higher prevalence of AHT was found in the HGZMF No.2 than the national average of 31.5%, with a significant percentage of uncontrolled patients. As well as associated risk factors such as age, gestational diabetes, cardiovascular history and smoking.

La Hipertensión Arterial (HTA) es un problema de salud pública por su alta prevalencia y como factor de riesgo para múltiples enfermedades. Objetivo: Establecer la prevalencia de HTA y factores de riesgo asociados en la población adulta del HGZ/MF No. 2 de Zacapu Michoacán. Material y Métodos: Estudio transversal, observacional y prospectivo. Realizado en el HGZ/MF No.2 de agosto a octubre 2022. Se aplicó el cuestionario MMM21 para conocer factores de riesgo, avalado por la Sociedad Internacional de Hipertensión Arterial. Se realizó estadística descriptiva y X2 para determinar asociación entre variables categóricas con valor significativo de p<0.05. Número de Registro: R-2022-1603-005. Resultados: Se estudiaron 325 sujetos, de los cuales 126 (38.77%) ya contaban con diagnóstico de HAS y 73 (22.45%) presentaba cifras de TA mayor a 140/90mmHg, encontrando una prevalencia total del 61.22%, predominando en el sexo femenino de 61-80 años. Como factores de riesgo asociados se encontró el tabaquismo, la diabetes gestacional, la edad y antecedentes de enfermedades cardiacas, siendo el IAM el de mayor frecuencia. De los 126 sujetos con diagnóstico de HAS, el 70.64% únicamente se encontraba controlado. Conclusiones: Se encontró una mayor prevalencia de HTA en el HGZMF No.2 que la media nacional de 31.5%, con un porcentaje importante de pacientes descontrolados. Así como factores de riesgo asociados como la edad, diabetes gestacional, antecedentes cardiovasculares y el tabaquismo.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16615; info:eu-repo/classification/cti/3; FCMB-E-2023-1677; Hipertensión arterial; Prevalencia; Factores de riesgo